2020
DOI: 10.3390/ijms21249547
|View full text |Cite
|
Sign up to set email alerts
|

Compounds with Antiviral, Anti-Inflammatory and Anticancer Activity Identified in Wine from Hungary’s Tokaj Region via High Resolution Mass Spectrometry and Bioinformatics Analyses

Abstract: (1) Background: Wine contains a variety of molecules with potential beneficial effects on human health. Our aim was to examine the wine components with high-resolution mass spectrometry including high-resolution tandem mass spectrometry in two wine types made from grapes with or without the fungus Botrytis cinerea, or “noble rot”. (2) For LC-MS/MS analysis, 12 wine samples (7 without and 5 with noble rotting) from 4 different wineries were used and wine components were identified and quantified. (3) Results: 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 130 publications
(152 reference statements)
0
2
0
Order By: Relevance
“…According to data published in the scientific literature, the type of grape utilized, the year of collection, and the type of microbes used for fermentation have a great influence on amino acid and biogenic amine content of grape-derived products [ 1 , 22 , 37 ]. Wine can be a rich source of amino acids and other compounds beneficial for our health [ 38 ], but due to its alcohol content, its consumption can be limited. Wine vinegar can be an alternative source of amino acids and biogenic amines, but to the best of our knowledge, no comparative analysis of wine and wine vinegar regarding their amino acid and biogenic amine content has been carried out so far.…”
Section: Resultsmentioning
confidence: 99%
“…According to data published in the scientific literature, the type of grape utilized, the year of collection, and the type of microbes used for fermentation have a great influence on amino acid and biogenic amine content of grape-derived products [ 1 , 22 , 37 ]. Wine can be a rich source of amino acids and other compounds beneficial for our health [ 38 ], but due to its alcohol content, its consumption can be limited. Wine vinegar can be an alternative source of amino acids and biogenic amines, but to the best of our knowledge, no comparative analysis of wine and wine vinegar regarding their amino acid and biogenic amine content has been carried out so far.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the preliminary experiments presented above ( Figure 6 ), with particular regard to the antioxidant investigations, we expected to obtain promising results from the gene expression tests. Kalló et al recently created a comprehensive functional data set related to the identified components of aszú wine, emphasising the importance of components with potential health benefits including anti-inflammatory effects [ 41 ]. However, relatively little data are available on the anti-inflammatory effect of extracts from Hungarian aszú wines.…”
Section: Discussionmentioning
confidence: 99%
“…2. Infection of grapes by Botrytis cinerea can cause an measurable increased value in the levels of caffeic acid, ethyl caffeate, ethyl gallate, fertaric acid, gentisic acid and quercetin [11].…”
Section: The Essential Of Phenolic Acid Producing Activity Of Yeastsmentioning
confidence: 99%